Dynamic Soil Properties for Microzonation of Delhi, India: A Review - Gaurav Kumar (International Journal of Modern Agriculture, 2021)
The city of Delhi in India has witness some minor seismic activities in the past as Delhi has come in the highly sensitive area for earth quake. The city Delhi, India’s capital, has witnessed minor seismic shaking in the past during many earthquakes .The broad differences in depths of the bedrock as well as groundwater table coupled with vegetation at various locations in Delhi need seismic microzonation analysis. Dynamic type soil such as shear velocity, modulus resultant as well as damping quality of soils are the specific and appropriate main contributions for conducting even a preliminary ground analysis, which is an necessary input in problems with concentration study; due to its soaring cost as well as lack of the required expertise, the shear wave velocity also isn’t determined systematically. Stress controlled cycle have tested on the molded sample by using the high voltage in combination of the silt mixture. These systems are used to generate modulus reduction and tested on the dumping configuration.